Influencing mechanism of buoyancy-induced micro-deformation on bubble horizontal transport along conical surfaces - Gao, Xiang; Ning, Hong-Yang; Song, Yunyun; Verdin, Patrick G.; Zhang, Fu-Jian; Zhang, Zhong-Qiang (American Institute of Physics (AIP), 2025)
Superhydrophobic conical surfaces exhibit significant potential in microfluidic manipulation and interfacial engineering due to their unique wettability and geometric constraints. However, previous studies have focused on steady-state bubble transport capacity on cone surfaces, overlooking the critical role of bubble morphology evolution in dynamic performance. Herein, a fluorinated silica nanoparticle suspension was synthesized and applied via spray-coating technology onto additively manufactured conical substrates, achieving simultaneous superhydrophobicity (water contact angle >150°) and exceptional bubble adhesion characteristics. Four stages of bubble transport on these surfaces were identified: (1) bubble-cone contact, (2) deformation and spreading, (3) maximum deformation and transition, and (4) stable transportation. A comparative analysis of bubble transport morphology across conical surfaces reveals that the transition stages 2 and 3, marked by maximum deformation and interfacial instability, play a pivotal role in determining overall transport efficiency. These observations were validated by COMSOL simulations, which showed consistent deformation times and revealed how bubble morphology influences migration velocity and pressure distribution. Notably, the double-cone structure enhanced transport efficiency by 62% over the single-cone design by simultaneously suppressing vertical bubble deformation and enhancing interfacial fluidity during the transition stages. Increasing the surface contact angle can enhance bubble transport velocity, whereas an increase in fluid viscosity slightly reduces the velocity. Simulations also show that cone arrangement strongly affects bubble transport, with vertical double-cones fastest and 30° configurations slowest. These findings offer practical insights for optimizing microfluidic devices and bubble collection systems, such as gas–liquid separators or microreactors, requiring precise hydrodynamic control.
Keywords: 40 Engineering; Fluids & Plasmas; 49 Mathematical sciences; 51 Physical sciences; Ultrahydrophobicity; Interfacial instability; Gas liquid interfaces; Buoyancy; Bubble dynamics; Microfluidic devices